Vital force as a triangulated concept of nature and s(S)pirit - Nalwamba, Kuzipa M. B. (HTS teologiese studies, 2017)
This article explores and seeks to appropriate theologically the African notion of vital force as a relational, non-reductionist ecological concept that would enrich the Christian doctrine of pneumatheology. The understanding that relational and pneumatological categories are viable within the theology–science dialogue is the broader framework within which this article is conceived. The relationship between natural theology and revelation provides an epistemological standpoint that does not divorce Spirit and reality.